Preceptor Facilitated Debriefing Improves Athletic Training Student's Clinical Performance and Work Efficacy - Jordan J. West; Kara L. Kraus; Kirk J. Armstrong (Bowling Green State University, 2018)
Debriefing is an essential part of healthcare training that utilizes a planned conversation to allow clinicians to analyze their actions, thought processes, and emotions with the goal of improving patient care and outcomes. Debriefing requires two-way communications between the athletic training student and facilitating preceptor. The process is more than providing feedback on clinical performance, but a communication process that fosters reflective insight into of behaviors and decisions. Debriefing after patient care encounters has been shown to increase critical thinking, confidence, clinical skill and clinical reasoning. With this enhancement in cognition and behavior, debriefing allows the student to strengthen their own capabilities and efficacy, better preparing themselves for real time clinical practice. Facilitating effective debriefing is challenging for seasoned educators, as well as practitioners untrained to facilitate effective debriefing.